ANALYSIS OF 3D STRUCTURE OF THE PROTEIN OF HAEMOPHILUS INFLUENZAE BY HOMOLOGY MODELLING HELPS IN PREDICTING BINDING SITES FOR SUBSTRATE, LEADS TO DESIGN ANTIBIOTIC - Rasool, Dr Rehana; Shafiq, Maria; swati, Samina; Farid, Anila; Shoukat, Sofia; Jadoon, Madeeha (Journal of Ayub Medical College Abbottabad, 2024)
Background: Haemophilus influenza persists as a well-known root of ill health in children throughout the entire world. Before the introduction of the vaccine, Haemophilus influenza remained a well-known and eminent source of septic arthritis, pneumonia, and epiglottitis. Haemophilus influenza, Neisseria meningitides, and staphylococcus pneumonia spreads through respiratory droplets and cause diseases such as meningitis, pneumonia, and other secondary infections related to respiratory diseases. Objective was to analyze the 3D structure of the protein of Haemophilus influenzae by homology modelling to design antibiotics. Methods: For the effective study of protein, computational tools were used to investigate protein structure and function, Comprehensive microbial resource (CMR) for comparative modelling, Interproscan, BLAST for sequence similarity searching, MODELLER 9.10 for homology modeling, Procheck and Protein Structure Analysis (ProSA) software for assessing model quality and structural validation. Results: The model showed that it consists of three alpha helices (red) and one beta-sheet. Ramachandran Plot statistics show that 97.4% of the debris is in the favoured region, 0% in the additional allowed region, 2.65% in the generally allowed part, and 0% in the disallowed part. Stability and energy were checked through ProSa. Z score was highly negative which showed that the model is highly stable. The greater the negative value, the more will be the stability of the model. Conclusion: Cell division protein H11025 was selected. The structure was modelled which has provided all the required information to design antibiotics to control the harmful effects regarding that protein.